Neoliberal reform in Machu Picchu : protecting a community, heritage site, and tourism destination in Peru - Luciano, Pellegrino A. (Lexington Books, 2018)
Pellegrino A. Luciano analyzes how people in Machu Picchu, Peru mobilized against neoliberal reforms. Luciano describes how they resisted and accommodated large capital investments and conservation efforts to protect their local tourism economy.